PERLINDUNGAN KONSUMEN TERHADAP PERDAGANGAN BAHAN BAKAR MINYAK (BBM) PERTAMINI ILEGAL DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Erinayustina Erinayustina; Jeane Neljte Sally (Fakultas Hukum Universitas Tarumanagara, 2022)
Natural wealth in the form of fuel must be managed properly, Law 22 of 2001 is here to manage it. Fuel management in downstream business licenses, including commercial activities. Prtamini does business illegally because it does not have permit, in addition to legality issues, negative impacts also arise, especially for consumers who use Pertamini’s fuel oil. The need consumer protection for Pertaminni business actors. The research method used is normative juridical research with analytical descriptive specifications, the data collected is secondary data and data analysis tecnique use descriptive qualitative techniques. BBM management must go through a legal mechanism to ensure legal certainty. In the Pertamini case, there was legal uncertainty, which means it violated the basic conception of a rule of law that guarantees legal certainty, because Pertamini does not have legality in accordance with the mandate of the Oil and Gas Law. Apart from not implementing legal certainty, the state’s omission of Pertamini actually causes harm to consumers, due to the lack of supervision over Pertamini which makes them mix or mix BBM at will which cause damage to vehicle engines and also unreasonable price games. Pretamini’s presence turned out to be the impact of the uneven distribution of fuel in remote areas which made business actors run the business considering it could bring profits. Therefore the Government needs to pay attention to this matter by cooperating with agencies.